2021
DOI: 10.1200/jco.2021.39.15_suppl.3020
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of CB-103, a novel first-in-class inhibitor of the CSL-NICD gene transcription factor complex in human cancers.

Abstract: 3020 Background: CB-103 selectively inhibits the CSL-NICD interaction leading to down-regulation of CSL-NICD mediated oncogenic pathway activation downstream of NOTCH receptor/ligand signaling, and has shown potent anti-cancer activity as single agent and in combination with targeted/chemotherapies in preclinical models. The aim of this dose escalation/expansion phase 1/2a study is to assess safety, maximum tolerated dose (MTD) and recommended phase 2 dose (RP2D), preliminary activity, pharmacokinetics and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Nevertheless, CB-103 had no anticalcific effect. While crenigacestat is gamma-secretase inhibitor, CB-103 is target to suppression of Notch transcription factor complex ( 11 , 12 ). Gamma-secretase inhibitors often have off-targets while gamma-secretase, in turn, has a wide list of targets besides Notch ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, CB-103 had no anticalcific effect. While crenigacestat is gamma-secretase inhibitor, CB-103 is target to suppression of Notch transcription factor complex ( 11 , 12 ). Gamma-secretase inhibitors often have off-targets while gamma-secretase, in turn, has a wide list of targets besides Notch ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…CB-103 is a small molecule selective inhibitor of the CSL-NICD complex. This complex activates Notch-target genes, so its inhibition leads to interruption of Notch signal transmission ( 11 ). Crenigacestat (LY3039478) is a small molecule selective inhibitor of Notch cleavage that suppresses Notch signal transduction by preventing the release of NICD ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies have demonstrated that CB‐103‐mediated inhibition of CSL‐NICD complex circumvents dose‐limiting toxicities associated with previous generations of NOTCH inhibitors, i.e., Gamma Secretase Inhibitors (GSIs) and monoclonal antibodies against NOTCH ligands and receptors (MABs) [ 2 ]. CB‐103 displayed an excellent safety profile in a Phase 1 dose‐escalation study in patients with solid tumors [ 12 ], notably with absence of toxicities typically associated with GSIs and MABs. Treatment with CB‐103 as a single agent in patients with NOTCH‐activated, metastatic adenoid cystic carcinoma resulted in cases with tumor regression, stop of growth, and long‐term disease control in patients with documented PD before treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Median PFS was 21.7 weeks, representing a clear clinical benefit in this patient population with fast‐progressing tumors. NOTCH pathway biomarkers in surrogate tissues showed strong target engagement [ 12 ].…”
Section: Introductionmentioning
confidence: 99%